2014
DOI: 10.1155/2014/537157
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolomic Profiling of Overweight Adolescents: An Elucidation of the Effects of Inter-/Intraindividual Differences, Gender, and Pubertal Development

Abstract: The plasma and urine metabolome of 192 overweight 12–15-year-old adolescents (BMI of 25.4 ± 2.3 kg/m2) were examined in order to elucidate gender, pubertal development measured as Tanner stage, physical activity measured as number of steps taken daily, and intra-/interindividual differences affecting the metabolome detected by proton NMR spectroscopy. Higher urinary excretion of citrate, creatinine, hippurate, and phenylacetylglutamine and higher plasma level of phosphatidylcholine and unsaturated lipid were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
7
32
0
Order By: Relevance
“…However, this result, as well as higher citrate excretion in females, corroborates a previous study on sex differences in children of 12–15 years old26 and adults27. These results should be corroborated in a larger study.…”
Section: Discussionsupporting
confidence: 91%
“…However, this result, as well as higher citrate excretion in females, corroborates a previous study on sex differences in children of 12–15 years old26 and adults27. These results should be corroborated in a larger study.…”
Section: Discussionsupporting
confidence: 91%
“…and overall bacteria attachment and colonization (43,44). A different stimulation of gut-bacteria activity after intake of either milk or cheese was suggested in a recent metabolomics study that showed that the microbiota-related metabolite hippurate was significantly higher in participants who ate cheese than in milk consumers and control participants (45). In the same study, cheese consumption was associated with an increased concentration of short-chain fatty acids in the gut, which was possibly induced by gut-microbiota modulation.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it cannot be excluded that disease biomarkers are potentially biased by a sexspecific metabolism. Zheng et al [70] state that it is the pubertal stage, representing a critical time period regarding body development and body composition that is affected by the obesity epidemic, although this relationship is not yet clarified. In their study of pubertal boys and girls, they found differences between the sexes mainly in lipoproteins, PC, unsaturated lipids, and lower levels of choline in girls.…”
Section: Sex Differences and Puberty Effectsmentioning
confidence: 99%
“…Tanner stage was also associated with different metabolite concentrations, especially creatinine and citrate. The authors suggest that this is due to the muscle turnover, as girls enter puberty earlier than boys and therefore might have had a higher muscle mass [70] .…”
Section: Sex Differences and Puberty Effectsmentioning
confidence: 99%